ANALISIS LINGKUNGAN SITUASIONAL TERHADAP PEMILIHAN TEMPAT BERBELANJA DI MINIMARKET lNDOMARET DI JL. P. SURYANATA OUTLET NO. 2 KOTA SAMARINDA - Taghfirul Azhima Yoga 3, Muhammad Aldi Ripani 1, Robin Jonathan 2, (EKONOMIA, 2020)
Muhammad Aldi Ripani, Situational Environmental Analysis of the Choice of Places to Shop at the Indomaret Minimarket on Street Pangeran Suryanata Outlet No.2 Samarinda City. Under the guidance of Mr. Robin Jonathan as the first mentor and Mr. Taghfirul Azhima Yoga Siswa as the second mentor.The purpose of this study includes knowing 1) the physical environment influences the selection of shopping places. 2) The social environment influences the selection of shopping places. 3) Time perspective influences the choice of shopping place. 4) Purchase objectives affect the selection of shopping places. 5) The preceding situation has an effect on the selection of shopping places. 6) Physical environment, social environment, time perspective, purchase objectives and conditions that precede together affect the selection of shopping places.The population type of this study is unknown population. The population consists of all those who shop at Indomaret on Street Pangeran Suryanata Outlet No.2 Samarinda City. The sampling technique used in this study was through a non probability sampling approach, namely purposive sampling with a total sample of 100 people using calculations using the Lameshow formula. This study uses a multiple linear regression analysis tool with the F test and t test using the SPSS V23 program.            The results of this study indicate that 1) The physical environment does not have a significant effect on the selection of shopping places. 2) The social environment has a significant influence on the selection of shopping places. 3) Time perspective has a significant influence on the selection of shopping places. 4) The purpose of the purchase has a significant influence on the selection of shopping places. 5) The situation that precedes does not have a significant influence on the selection of shopping places. 6) Physical environment, social environment, time perspective, purchase purpose, predating conditions together have a significant effect on the selection of shopping places